Zoning landscape of the Hacienda el Ocaso, Quimbaya, Quindío (Revista de Investigaciones Universidad del Quindío, 2010)
The natural reserve “The Mountain of Ocaso” is part of the Hacienda El Ocaso. Actually, it is the mayor relict of the natural forest preserved in the low land of the department of Quindío with 148.84 ha. In order to contribute to the model of conservation that the University of Quindío is realizing in this area, as an objective to be realized, it is proposed to realize characterization and landscaping zonification of the land use within the reserve. From March of 2008 until February of 2010 the cartography of the area was actualized, taking as a base one aerial photo and the exploration of the site of the interest. The maps of the vegetation cover and the actual land use were elaborated as well as maps of the areas of the interest for investigation and conservation, and a series of forest corridors which communicate fragmented are as with the biggest fragment of forest. With in the natural vegetation the presence of Guadua angustifolia and secondary vegetation without the presence of G. angustifolia is found. In some places of the secondary forest it is observed the combination of the presence of the G. angustifolia and the natural vegetation. In the last ten years it is observedan increment of more than 50% of the Guadua angustifolia with in the reserve and also outside of the reserve. The protected area of the forest increased up to 42.84 ha from the time of the last recordin 2007.
Keywords: Landscaping zonification; natural reserve; land use; vegetable diversity; Vegetation Cartography; Andes of Colombia